2015
DOI: 10.1017/s0029665115001676
|View full text |Cite
|
Sign up to set email alerts
|

Food and the consumer: could labelling be the answer?

Abstract: Extensive research into the impact of nutrition labelling across Europe has shown that many consumers can effectively use a nutrition label to rank a food for healthiness. The present paper considers observational and laboratory evidence which has examined the impact of nutrition labelling (on food packaging and at point of purchase) on dietary behaviour. In addition, the potential counterproductive effects of foods bearing 'healthy' nutrition labels are examined. The observational evidence provides a useful i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
(71 reference statements)
1
20
0
1
Order By: Relevance
“…It also provides further evidence that external information about the healthfulness of foods affects restrained eaters' consumption more than that of unrestrained eaters. 21 These findings are consistent with findings by Dovey et al, 60 who found that restrained eaters were more heavily influenced by food advertising messages than unrestrained eaters, and findings by Kerr et al, 61 who found that individuals on a weight-loss diet were among the most likely to use nutrition labels, increasing the tendency to overeat foods they perceived to be more healthful. Two studies found information on labels impacted on the consumption behavior of unrestrained but not restrained eaters.…”
Section: Discussionsupporting
confidence: 83%
“…It also provides further evidence that external information about the healthfulness of foods affects restrained eaters' consumption more than that of unrestrained eaters. 21 These findings are consistent with findings by Dovey et al, 60 who found that restrained eaters were more heavily influenced by food advertising messages than unrestrained eaters, and findings by Kerr et al, 61 who found that individuals on a weight-loss diet were among the most likely to use nutrition labels, increasing the tendency to overeat foods they perceived to be more healthful. Two studies found information on labels impacted on the consumption behavior of unrestrained but not restrained eaters.…”
Section: Discussionsupporting
confidence: 83%
“…As consistent and simple serving size information on nutrition labeling is considered an important strategy to facilitate healthy food choices and intake 21 , it is relevant to analyze how serving sizes are declared on processed food labels in Brazil. Considering the lack of studies in Brazil assessing serving size declaration and the allowed variation by the Brazilian law, the aim of this study was to analyze the serving sizes declared on Brazilian food labels with respect to their conformity to Brazilian law, variability among similar foods and relationship to energy value.…”
Section: Introductionmentioning
confidence: 99%
“…The increasing consumer’s attention on knowing about what we eat and the mandatory of nutrition labeling by the industry, has increased the need to produce more complete composition data [ 25 , 26 ]. On the other hand, the poor availability of data for specific food formulations, often on the market for a short time, clearly indicates the need to study alternative methods to analytical methods to know their nutritional properties.…”
Section: Nutritional Composition Of Composite Foods: Comparing Anamentioning
confidence: 99%